Representations of war in the poetry of Iraqi poetry (2003 - 2012) - ., Hutham bader (Al-Adab Journal, 2015)
Iraq has faced many wars along the past four decades. As a result, its people, especially its women and poetesses specifically have lived in horrible and terrible circumstances. Wars have entered each Iraqi house, from the gates of killing, kidnapping and immigrating.The woman is still the big loser in these wars, because they have given her successive losses which put huge pressures over her and excluding her rights extensively. This exclusion has been represented through the book of (Fear’s Circle) by “Nasr Hamid Abu Zaid”. He sees that when nation’s mind has suffered from freezing, this will reflect automatically on woman’s soul, mind and body, as she is considered as the weakest part who reflects defeat and cognitive social retreat. The repetition of losses awakens racial and tribal ideas and refreshes them with dictatorial speech which refuses to listen to others and rejects conversation. This speech has the concept of definite fact possession, and it assumes having a divine authority. Whether this speech is social or political, the result is enslaving individuals (Man & Woman) and insulting them. This insult will be doubling on woman and child.Iraqi poetesses have adopted this theme, and functioned it in their creative poetic field through the use of war topic and its equalizes in their poems and expressing their points of view according to what are happening around then, especially the civil violence in Iraq, so I have chosen the period after 2003 events and its negative reflections on woman and the damage that expands in Iraq with the loss of security and peace.The research deals with three Iraqi poetesses that their poems concentrate on civil violence in Iraq:Reem Qais Kubba in her three collections: When will you believe that I’m a butterfly? (2005), Our Home (2009), the sea reads my luck (2010).Rana Ja’far Taseen in her two collections: Nails in Memory (2007), Painting with Unknown (2009).Faleeha Hassan in her collection: After a While (2007).The plan is divided into these topics:War and poetry.Woman and language.Woman and her social life.The research contains conclusions and summery.